The role of hemodynamic catheterization in the evaluation of hypertrophic obstructive cardiomyopathy: A case series. Issue 5 (18th February 2015) - Bishu, Kalkidan; Coylewright, Megan; Nishimura, Rick
<x xml:space="preserve">Abstract</x> Confirmation of the presence and magnitude of left ventricular outflow tract (LVOT) obstruction is a critical component of the evaluation of symptoms in patients with hypertrophic cardiomyopathy (HCM). The presence of LVOT obstruction in patients with severe symptoms refractory to pharmacologic therapy identifies a subgroup of HCM patients who may benefit from septal reduction therapy. Two‐dimensional echocardiography with continuous wave Doppler is the main tool for confirming the presence and severity of LVOT obstruction in HCM. However, when uncertainty remains following non‐invasive evaluation, invasive hemodynamics studies are required to confirm and quantify LVOT obstruction. In this manuscript we describe a series of 6 cases in which hemodynamic catheterization is instrumental in supplementing non‐invasive imaging in the assessment of LVOT obstruction in HCM. © 2015 Wiley Periodicals, Inc.